2015
DOI: 10.18805/lr.v0iof.9598
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters and combining ability analysis in blackgram [Vigna mungo (L.) Hepper]

Abstract: An experiment was carried out in blackgram using line x tester mating design to estimate the gca effect of parents (six lines and five testers) and sca effect of 30 hybrids for yield and its traits. Estimates of gca and sca variances, degree of dominance, predictability ratio and narrow sense heritability revealed that only three trais viz., pods per plant, seeds per pod and single plant yield were controlled by additive gene action and hence showed high narrow sense heritability. Magnitude of non-additive gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
4
5
0
Order By: Relevance
“…The crucial importance of both additive and non-additive gene effects for inheritance of characters was also supported by Barad et al 2007, Selvam and Elangaimannan, 2010, Patil et al 2011, Nath et al 2018and Samantaray et al 2018 As apprehended from the ratio of σ 2 gca and σ 2 sca (Table 3), there was preponderance of additive gene action for the characters viz., days to 50% flowering, days to maturity and pod length and rest of the characters exhibited non-additive gene action. The characters exhibiting additive gene action were in agreement with the findings of Priya et al2012 andThamodharan et al 2017. The non-additive type of gene action for yield characters was confirmed by Selvam and Elangaimannan, 2010, Narashimulu et al 2014and Gill et al 2020.…”
Section: Resultssupporting
confidence: 88%
“…The crucial importance of both additive and non-additive gene effects for inheritance of characters was also supported by Barad et al 2007, Selvam and Elangaimannan, 2010, Patil et al 2011, Nath et al 2018and Samantaray et al 2018 As apprehended from the ratio of σ 2 gca and σ 2 sca (Table 3), there was preponderance of additive gene action for the characters viz., days to 50% flowering, days to maturity and pod length and rest of the characters exhibited non-additive gene action. The characters exhibiting additive gene action were in agreement with the findings of Priya et al2012 andThamodharan et al 2017. The non-additive type of gene action for yield characters was confirmed by Selvam and Elangaimannan, 2010, Narashimulu et al 2014and Gill et al 2020.…”
Section: Resultssupporting
confidence: 88%
“…This indicated that the trait was controlled by a duplicate type of non-allelic interaction. It was in accordance with the findings of Thamodharan et al (2017); Vadivel et al (2019).…”
Section: Number Of Clusters/plantsupporting
confidence: 92%
“…However in case of MDU1 x Mash 1008, in addition to additive, dominance components, epistatic component of dominance x dominance was also important. Similarly Kanchana Rani ( 2008) and Thamodharan et al, (2015) recorded additive and non-additive gene action respectively.…”
Section: Plant Height (Cm)mentioning
confidence: 97%
“…Similarly additive gene action was reported by Kanchana rani (2008) and Latha et al, (2018). Non-additive gene action was reported by Thamodharan et al, (2015). `…”
Section: Number Of Clusters Per Plantmentioning
confidence: 99%
See 1 more Smart Citation